Social Security Protection Policy: in a Legal Approach - Fatkhul Muin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Paradigam base in frame support effort For create good system​ Social security lies in the commitment of the state within effort follow as well as For create system social security for society , so that you can protected from fundamental problems such as health and social protection of employment . An interesting fact , the existence and position of Indonesia as a developing country , of course need balanced internal state capabilities frame create protection social security for citizen . Law no. Constitution Republic of Indonesia Number 24 of 2011 concerning Organizing Bodies Social Security is a basic instrument in effort protection social in in the field of health and employment . Scope​ in guarantee social the in essence become hope in frame create system guarantee good social​ in accordance with mandate the country's constitution concrete instruct to the country for responsible in frame protection limited every citizen . In study This aim For analyze policy protection guarantee social state with legislative regulatory approach .